Got forages? Understanding potential returns on investment in Brachiaria spp. for dairy producers in Eastern Africa - Schiek, Benjamin E.; Gonzalez Rodriguez, Carlos Eduardo; Mwendia, Solomon W.; Prager, Steven D. (International Center for Tropical Agriculture, 2018)
Production of livestock and dairy products in Sub-Saharan Africa struggles to keep pace with growing demand. The potential exists to close this gap in a climate-friendly way through the introduction of improved forage varieties of the Brachiaria genus. We assess the potential economic impact of the development and release of such varieties in 6 Eastern African countries using an economic surplus model. Results are presented across a range of potential scenarios involving different adoption rates and percentage increases in production. For all but the lowest levels of adoption and production increases, improved forages have the potential for positive return on investment. Using these results, we present formulae that help readers calculate the adoption rate or percentage increase in production necessary to achieve specific desired levels of net benefit. Overall, the model output suggests that investment in a forages research program related to the qualities of the forage itself as well as programs to enhance dissemination and adoption of new materials would be low risk and have high likelihood for positive outcomes, generating discounted net benefits in the order of multiple tens of millions of dollars over a 30-year time horizon.